2004
DOI: 10.1002/eji.200424819
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal and splenic B‐1 cells are separable by phenotypic, functional, and transcriptomic characteristics

Abstract: B-1 cells constitute a distinct B cell population with unique phenotypic and functional characteristics. Although the origin of B-1 cells remains controversial, B-1 cells in different locations are generally considered to be part of the same pool. To determine the validity of this assumption, we examined peritoneal and splenic B-1 cells isolated by flow cytometric cell sorting from normal mice for several features. We found that splenic B-1 cells differ from peritoneal B-1 cells in terms of surface antigen exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
71
0
3

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 50 publications
11
71
0
3
Order By: Relevance
“…4 and depict the means of four independent experiments. We found that the majority of splenic B-2 cells did not survive 3 days in culture, as expected [23], with 36 AE 2.8% (mean AE SEM, n = 4) viability at the end of the incubation. In contrast, peritoneal B-1 cells remained largely viable over the entire culture period (76 AE 6.2%), also as expected [23].…”
Section: Peritoneal B-2 Cells Survive and Secrete Igm In Vitrosupporting
confidence: 84%
See 2 more Smart Citations
“…4 and depict the means of four independent experiments. We found that the majority of splenic B-2 cells did not survive 3 days in culture, as expected [23], with 36 AE 2.8% (mean AE SEM, n = 4) viability at the end of the incubation. In contrast, peritoneal B-1 cells remained largely viable over the entire culture period (76 AE 6.2%), also as expected [23].…”
Section: Peritoneal B-2 Cells Survive and Secrete Igm In Vitrosupporting
confidence: 84%
“…We found that the majority of splenic B-2 cells did not survive 3 days in culture, as expected [23], with 36 AE 2.8% (mean AE SEM, n = 4) viability at the end of the incubation. In contrast, peritoneal B-1 cells remained largely viable over the entire culture period (76 AE 6.2%), also as expected [23]. In addition to enhanced survival, B-1 cells spontaneously secrete IgM when placed in culture for several days [29].…”
Section: Peritoneal B-2 Cells Survive and Secrete Igm In Vitrosupporting
confidence: 84%
See 1 more Smart Citation
“…2D). In contrast, although CD80 expression on B1p cells is greatly increased over that of B2s cells [19], anti-CD80 antibody had much less effect on the capacity of B1p cells to stimulate alloreactive T cells than did anti-CD86 antibody (Fig. 2C) and failed to reverse the poor iT reg induction by B1p and B2p cells (Fig.…”
Section: Enhancement Of It Reg Induction By Costimulation Blockadementioning
confidence: 92%
“…To test this, blocking antibodies for CD80 and CD86 were added during iT reg induction. Although CD86 expression on B1p cells is only modestly increased over that of B2s cells [19], anti-CD86 antibody markedly reduced the capacity of B1p (and B2p) cells to stimulate alloreactive T cells (Fig. 2C); conversely, anti-CD86 antibody dramatically increased the capacity of B1p (and B2p) cells to convert Foxp3 -CD4 + T cells to the Foxp3 + phenotype (Fig.…”
Section: Enhancement Of It Reg Induction By Costimulation Blockadementioning
confidence: 96%